Trends in Research of Prenatal Stress From 2011 to 2021: A Bibliometric Study - Dong, Yankai; Chen, Shengquan; Wang, Zhifei; Ma, Yao; Chen, Jinfeng; Li, Ge; Zhou, Jiahao; Ren, Yating; Ma, Hengyu; Xie, Juanping; Li, Hui; Zhu, Zhongliang (Frontiers in Pediatrics, 2022)
Background: Maternal stress during pregnancy can increase the risk of mental disorders of their offspring. The continuous emergence of clinical concepts and the introduction of new technologies are great challenges. Through bibliometric analysis, the research trends and hotspots on prenatal stress were explored to comprehend clinical treatments and recommend future scientific research directions. Methods: Studies on prenatal stress published on the Web of Science Core Collection (WoSCC) database between 2011 and 2020 were reviewed. Bibliometric analysis was conducted according to the number of articles, keywords, journals, citations, affiliations and countries. With the data collected from the WoSCC, visualisation of geographic distribution, clustering analysis of keywords, affiliations and authors, descriptive analysis and review of co-cited references were carried out. Results: A total of 6,949 papers published in 2011–2020 were retrieved. During this period, the number of publications increased. Psychoneuroendocrinology is the leading journal with the most publications on prenatal stress. The largest contributor was the US. The University of California System was the leading amongst institutions conducting relevant research. Wright RJ, King S and Laplante DP were scholars with significant contributions. Hotspots were classified into five clusters, namely, pregnancy, prenatal stress, oxidative stress, schizophrenia and exposure. Conclusions: The number of studies on prenatal stress increased. Journals, countries, institutions, researchers with most contribution and most cited articles worldwide were extracted. Studies have mostly concentrated on the treatment of diseases, the application of new technologies and the analysis of epidemiological characteristics. Multidisciplinary integration is becoming the focus of current development. Intestinal flora and epigenetics are increasingly used in studies on prenatal stress. Thus, they constitute a solid foundation for future clinical medicine and scientific research.